Positive Effects of Neutrophil Elastase Inhibitor (Sivelestat) on Gut Microbiome and Metabolite Profiles of Septic Rats - Sun, Yali; Ding, Xianfei; Cui, Yuqing; Li, Hongyi; Wang, Dong; Liang, Huoyan; Liu, Shaohua; Zhang, Xiaojuan; Wang, Haixu; Sun, Tongwen (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Neutrophil elastase (NE) is associated with sepsis occurrence and progression. We hypothesized that the NE inhibitor Sivelestat might modulate abnormal gut microbiota and metabolites during sepsis. Methods: Sixty Sprague-Dawley (SD) rats were randomly divided into sham control (SC), sepsis (CLP), and sepsis+Sivelestat (Sive) groups. The rats’ survival status was monitored for 24 hours postoperatively, and feces were collected for microbiome and non-targeted metabolomics analyses. Results: Sivelestat administration significantly improved the survival of septic rats (80% vs. 50%, P = 0.047). Microbiome analysis showed that the microbiota composition of rats in the CLP group was significantly disturbed, as potential pathogens such as Escherichia-Shigella and Gammaproteobacteria became dominant, and the beneficial microbiota represented by Lactobacillus decreased. These changes were reversed in Sive group, and the overall microbial status was restored to a similar composition to that of the SC group. Differential analysis identified 36 differential operational taxonomic units and 11 metabolites between the Sive and CLP groups, including 6-Aminopenicillanic acid, gamma-Glutamyl-leucine, and cortisone (variable importance in projection＞1and P＜0.05). These discriminatory metabolites were highly correlated with each other and are mainly involved in the phenylalanine, tyrosine, and tryptophan biosynthesis pathways. Integrated microbiome and metabolome analyses found that almost all Sivelestat-modulated microbes were associated with differential metabolites (P < 0.05), such as Lactobacillus and some amino acids, suggesting that the Sivelestat-induced metabolic profile differences were in part due to its influence on the gut microbiome. Conclusion: Sivelestat administration in septic rats improved survival, and gut microbiota composition, and associated metabolites, which could provide new options for sepsis treatment.